2017
DOI: 10.1261/rna.060715.117
|View full text |Cite
|
Sign up to set email alerts
|

Microprocessor dynamics shows co- and post-transcriptional processing of pri-miRNAs

Abstract: miRNAs are small regulatory RNAs involved in the regulation of translation of target transcripts. miRNA biogenesis is a multistep process starting with the cleavage of the primary miRNA transcript in the nucleus by the Microprocessor complex. Endogenous processing of pri-miRNAs is challenging to study and the in vivo kinetics of this process is not known. Here, we present a method for determining the processing kinetics of pri-miRNAs within intact cells over time, using a pulse-chase approach to label transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…To determine the splicing kinetics of newly transcribed RNA, we used BrU-pulse-chase sequencing as described (Louloupi et al, 2017; Paulsen et al, 2013). In brief, cells were labeled with a 15 minutes BrU pulse and chased for 0, 15, 30 and 60 minutes followed by RNA purification.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the splicing kinetics of newly transcribed RNA, we used BrU-pulse-chase sequencing as described (Louloupi et al, 2017; Paulsen et al, 2013). In brief, cells were labeled with a 15 minutes BrU pulse and chased for 0, 15, 30 and 60 minutes followed by RNA purification.…”
Section: Resultsmentioning
confidence: 99%
“…Their processing by the Microprocessor is a key step and requires a high degree of precision because it defines the miRNA ends and even a single‐nucleotide deviation can affect which mRNAs are targeted. In addition, global analysis of pri‐miRNA processing in vitro and in vivo showed that the nuclear processing event predominantly explains the differential accumulation of miRNAs . It is therefore essential to understand how the Microprocessor discriminates between authentic substrates and the rest of the countless stem‐loop RNA structures in the cell.…”
Section: Nuclear Processing Of Primary Mirnasmentioning
confidence: 99%
“…They showed that processing efficiency varies among the different pri‐miRNA substrates and correlates with endogenous miRNA expression and that conserved pri‐miRNAs are better substrates of the Microprocessor. Recently, the Orom laboratory developed a transcriptome‐wide approach using next‐generation sequencing to determine in vivo kinetics of pri‐miRNA processing . In a first study, they sequenced pri‐miRNAs purified by chromatin immunoprecipitation.…”
Section: Nuclear Processing Of Primary Mirnasmentioning
confidence: 99%
“…The nuclear microprocessor complex consisting of Drosha and two molecules of its co-factor DGCR8 cleaves the pri-primary (pri-)miRNAs to give rise to a ~60nt stem-loop pre-miRNAs (9,10). Specific sequence motifs within the pri-miRNA have been shown to affect the pri-miRNA cleavage efficiency, including the apical GUG/UGU, a GC and UG motifs 13nt and 14nt upstream of the Drosha cleavage site, respectively, and a CNNC motif 16-18nt/16-24nt downstream of the Drosha cleavage site (11)(12)(13)(14)(15). The CNNC motif was previously identified as the consensus binding motif for Serinearginine rich splicing factor 3 (SRSF3), an RNA binding protein (RBP) with multiple functions in mRNA metabolism (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Although polycistronic miRNAs are critical in human development, homeostasis and disease, we know surprisingly little of how their processing is regulated post-transcriptionally. Importantly, miRNAs produced from a common primary transcript are present at highly varying levels in cells and tissues, suggesting that the processing of individual miRNAs within the cluster can be differentially regulated (11,21,22). For example, hnRNPA1 was shown to specifically bind to the conserved terminal loop of miR-18a within miR-17-92 cluster and promote its processing independent of other miRNAs of the cluster (22).…”
Section: Introductionmentioning
confidence: 99%